(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2017)
This essay examines the meaning of the legal term symbolaion, the interpretation of the law about maritime cases (dikai emporikai), and the use of the paragraphe procedure in maritime cases. The first part shows through a careful examination of the passages in which the term symbolaion is found that the word does not mean “contract” but in legal contexts designates all “actionable liabilities” arising either from a delict or from breach of contract or “disputes about such liabilities.” The second part shows that the law about maritime cases applied broadly to disputes about actionable liabilities aris- ing from delicts and from breaches of contract incurred by merchants and ship-owners in the port of Athens and on voyages from and to Athens. The third applies this new understanding of the law about mercantile suits and the use of the paragraphe to the demosthenic speeches Against Zenothemis, Against Apaturius, Against Phormio, and Against Lacritus and provides a better understanding of the legal issues in these cases. The final section also demonstrates that parts of these speeches that scholars have con- sidered irrelevant to the main legal issues are in fact directly relevant to the task of proving the legal charges and sheds new light on the legal procedure of paragraphe.